From the History of Art and Design Education at Kharkiv Art and Industrial Institute: Gradual Transition from Industrial Graphics to Graphic Design (1973–1985) - Galchenko, Valeriy (HUDPROM: The Ukrainian Art and Design Journal, 2024)
This article examines the second decade of the Department of Industrial Graphics and Packaging (IGP) at the Kharkiv Art and Industrial Institute (KhAII) (now the Department of Graphic Design at Kharkiv State Academy of Design and Arts (KSADA)) during the years 1973–1985. This period largely coincides with the tenure of Rector Ye. Yegorov. At that time, one of the department’s key figures was the talented graphic artist and associate professor V. Nenado. Nenado played a crucial role in inviting young graduates of the IGP Department – O. Veklenko, V. Shevchenko, and later O. Blyakher and V. Lesnyak – who contributed to a rapid breakthrough into a new dimension of applied graphics, including graphic design, packaging, contemporary poster art, and book design. This study is based on archival materials from KSADA, photo archives from the Department of Graphic Design, private collections of IGP graduates from various years, and testimonies from faculty and former students of the Department of Industrial Graphics. From the department’s inception, two distinct developmental vectors emerged. One was aimed at transforming traditional industrial graphics into a more modern communicative design, while the other focused on reviving classical easel graphic arts, such as printmaking, book illustration, and poster design. A significant milestone occurred in September 1983 when the “Graphics” subsection, which specialized in training political poster artists, was restructured into an independent “Graphics” department with broader academic authority. Associate Professor V. Vikhtinsky was appointed as its head, while Associate Professor A. Kuzmenko took over leadership of the IGP Department. This division marked the definitive separation of easel and applied graphics within KhAII (now KSADA). As a visual accompaniment to this article, selected fragments of the best diploma projects from the 1970s through the first half of the 1980s are presented. According to the author, diploma projects serve as the most vivid representation of student achievements, encapsulating their skills, artistic growth, and methodological training. These works also reflect the distinctive artistic and pedagogical qualities of the institution and its leading educators.